Naturally derived injectable hydrogels with ROS-scavenging property to protect transplanted stem cell bioactivity for osteoarthritic cartilage repair - Li, Haobo; Xiang, Dong; Gong, Chongcheng; Wang, Xiaomin; Liu, Lin (Frontiers in Bioengineering and Biotechnology, 2023)
Intra-articular injection of adipose mesenchymal stem cells (ADSCs) is a potential alternative to the treatment of osteoarthritis (OA) and has aroused great interest of clinical researchers. However, the hostile microenvironment in the joint cavity, characterized by reactive oxygen species (ROS) accumulation and excessive inflammation, disturbs the bioactivity of the transplanted stem cells. The (-)-epigallocatechin-3-O-gallate (EGCG), a green tea catechin, has attracted the researchers’ attention owing to its powerful ROS-scavenging and antioxidant properties. In this study, to avoid rapid degradation and/or depletion of EGCG, we prepare a long-lasting injectable hydrogel by EGCG and hyaluronic acid (HA). The naturally derived hydrogels with excellent biocompatibility and durable retention time can capture the redundant ROS continuously and efficiently, thus protecting ADSCs from ROS-mediated death and bioactivity inhibition, including cell survival, proliferation and chondrogenic differentiation. Intra-articular injection of this ADSCs loaded hydrogel significantly induced synovial macrophages polarization to M2 phenotype, decreased pro-inflammatory cytokines (e.g., IL-1β, MMP-13, and TNF-α) expression, promoted cartilage matrix formation, and repaired cartilage destruction in OA. This stem cell-protected hydrogel delivery strategy showed superior efficacy than ADSCs delivering or EGCG-HA injection singly, which providing a potential alternative strategy for OA management.